THE RELATIONSHIP BETWEEN THE PROVISION OF SAFE WATER FOR CHILDREN UNDER FIVE YEARS OF AGE AND THE INCIDENCE OF DIARRHEA IN WEST NUSA TENGGARA - Hamdan (Perhimpunan Kesehatan Holistik Indonesia, 2021)
In developing countries such as Indonesia, diarrhea is still a public health problem because of its high morbidity and mortality. According to the West Nusa Tenggara Health Office, the prevalence of diarrhea cases in West Nusa Tenggara is 19,232, one of which is the contamination of drinking water in the community